MS pipe for conduiting for AV. PA, IT system, security access control and fire detection cabling work - Brac University (Brac University, 2023)
This record consists of general correspondence regarding MS pipe for conduiting for AV. PA, IT system, security access control and fire detection cabling work of BRAC University new campus project.